2015
DOI: 10.1080/17470919.2015.1078258
|View full text |Cite
|
Sign up to set email alerts
|

Instructions of cooperation and competition influence the neural responses to others’ pain: An ERP study

Abstract: Neural activities triggered by viewing other's in pain have been previously reported to be modulated by various factors. How instructions of cooperation and competition can influence these activities has not been explored yet. In the current study, participants were instructed to play a game cooperatively or competitively with a partner. During the game, pictures showing an anonymous individual's hand or foot in painful or non-painful situations were randomly presented in an oddball style. The event-related po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 30 publications
2
36
1
Order By: Relevance
“…If the painful and the non-painful stimuli were differentiated in one condition (difference of amplitudes (P-NP) was significant) but not in another condition, we can say the stimuli was better processed in the former condition. In the literature, this logic has been applied widely 11,48,49 .…”
Section: Discussionmentioning
confidence: 99%
“…If the painful and the non-painful stimuli were differentiated in one condition (difference of amplitudes (P-NP) was significant) but not in another condition, we can say the stimuli was better processed in the former condition. In the literature, this logic has been applied widely 11,48,49 .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, while we can predict general patterns of modulation of ERP activity, the direction of these predicted effects is less clear. For example, while some studies find that observing another in pain VISUAL PERSPECTIVE AND EMPATHY FOR PAIN leads to smaller mean N2 amplitudes (e.g., Han et al, 2008;Li et al, 2010;Coll et al, 2017a), other studies have found larger N2 amplitudes (e.g., Suzuki et al, 2015;Cui et al, 2016a;2016b;2016c;2016d;Decety et al, 2017). In contrast, the P3/LPP has been more consistent, with all studies reviewed here (reporting significant effects relating to the P3/LPP) finding larger P3/LPP amplitudes during pain observation compared to no-pain.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it should be noted that the EEG hyperscanning acquisition was used in response to cognitive performance without a specific external feedback which may reinforce the effect of the joint-action (F. Cui, Zhu, Duan, & Luo, 2015;Dommer, Jäger, Scholkmann, Wolf, & Holper, 2012;Saito et al, 2010). Therefore, the present study aimed at moving towards a two-person hyperscanning by investigating the EEG correlates of between-brain synchrony during a joint task in presence of an external feedback related to the interpersonal joint performance.…”
Section: Introductionmentioning
confidence: 99%